IMPLEMENTASI UNDANG-UNDANG NOMOR 13 TAHUN 1998 DALAM MENINGKATKAN KESEJAHTERAAN LANSIA DI DINAS SOSIAL KABUPATEN MOJOKERTO - Kusuma Wardani, Anita; Muhaimin, Hikmah; Santosa (Government Studies Departement of Universitas Islam Majapahit, Indonesia, 2022)
Implementation is an action or implementation of a plan that has been arranged sequentially. Usually done afterpolicy planning that is considered perfect. In accordance with policies that include rules containing elements of decisions in an effort toselection of alternatives in order to achieve certain goals and objectives. In relation to the law that regulates the elderly, such as clothing, boardsand food. in Mojokerto Regency there is an institution that oversees all Regency Elderly who receive assistance from the government.Therefore, the elderly who have no family or are neglected will be put in a nursing home under the auspices of the Social Service which will provide services for the elderlyget protection and social security from the government. There is a budget from the APBD for every elderly in the nursing home. Destinationof this study is to determine the implementation of the welfare of the elderly according to the Law on the Elderly Number 13 of 1998. The results of the studyThe welfare of the elderly in nursing homes is measured by using 6 aspects, namely influencing interests, types of benefits,degree of change, location of decision making, program implementers and resources used.